A desalination system utilizing solar ambient and waste energy - Hawlader, M N A; Amin, Zakaria Mohd (2011)
Desalination is considered one of the most suitable areas for the utilization of solar energy, as there are many places in the world where abundant supply of solar energy is available and also there is a great demand for fresh water. An integrated solar heat pump desalination system is developed at the National University of Singapore (NUS), which also offers the opportunity of water heating and drying utilizing solar, ambient energy and waste heat from air-con, which is conventionally dumped to the environment causing global warming. Desalination is carried out by making use of MED (Multi-Effect Distillation) system. Within the MED chamber, both flashing and evaporation of saline water take place. The maximum Coefficient of Performance (COP) of the heat pump system was around 5.8. In the integrated system, the maximum fresh water production rate was 9.6 litres/hr with Performance Ration (PR) of 1.2. For only desalination, the system has the potential to produce a maximum of 30 liters/hr of fresh water.